The relationship between categories of selectors and usage of books in Miriam College Library with implications for collection development - Del Rosario, Emelita C. (1994)
This study was conducted in order to evaluate the effectiveness of the Miriam College Library selection methods. It determined if a difference exists between the two methods of selection (faculty selection and librarian selection) with regard to the usage of library books selected through them. Information was collected about some factors that can influence the use of materials. The study is based on the premise that faculty members are more effective book selectors than librarians because faculty members know the literature of their subject field's best.